Heidegger, Hölderlin e la poeticità del tempo (Comparatismi, 2025)
The article explores the dialogue between Heidegger and Hölderlin, showing how poetry becomes, for the German philosopher, the original site of temporal experience. In Hölderlin’s word, Heidegger recognizes a saying that transforms the interpreter, dissolving the distance between writer and thinker. Poetry, as authentic time, precedes all logic: it is the dwelling where language brings the world into being and thought rediscovers its “other beginning.”
Keywords: Heidegger; Hölderlin; Poetry; Time; Hermeneutics